2016
DOI: 10.1002/masy.201500154
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Polyethylene Blends Using Organomica

Abstract: This study aims to incorporate LLDPE into HDPE in order to improve its processability, as well as to employ a nanoclay for maintaining the HDPE stiffness. Thermal, dynamic-mechanical and rheological properties of polyethylene composites were investigated. Muscovite mica was treated with lithium nitrate for seven cycles, followed by exchange with quaternary ammonium salt to produce organomica. Initially, organomica was added to HDPE at 2% wt. using a tweenscrew mini-extruder. The blend HDPE/LLDPE (1:1 by weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…It was found that with increasing filler concentration the crystallinity of the HDPE in HDPE/mica composites increased from 59 % for virgin HDPE to 77 % for 15 w. % HDPE/mica composite, indicating a positive effect of the mica nano-sheets planar crystalline facets on HDPE crystallization in a similar fashion as in the case of other planar filler materials such as clay [6,21]. The observed maximum thermal degradation rate of the HDPE/mica composites found was about 467 °C, which was in agreement with the earlier published data [46]. On the other hand, the crystallinity decreased from 62 % obtained for virgin HDPE to 56 % for the 15 w. % HDPE/wollastonite composites.…”
Section: Resultssupporting
confidence: 90%
“…It was found that with increasing filler concentration the crystallinity of the HDPE in HDPE/mica composites increased from 59 % for virgin HDPE to 77 % for 15 w. % HDPE/mica composite, indicating a positive effect of the mica nano-sheets planar crystalline facets on HDPE crystallization in a similar fashion as in the case of other planar filler materials such as clay [6,21]. The observed maximum thermal degradation rate of the HDPE/mica composites found was about 467 °C, which was in agreement with the earlier published data [46]. On the other hand, the crystallinity decreased from 62 % obtained for virgin HDPE to 56 % for the 15 w. % HDPE/wollastonite composites.…”
Section: Resultssupporting
confidence: 90%
“…The fusion properties of the pellets of wood-HDPE particles (25,35, and 45% of wood particles by weight) were measured using a Haake PolyLab OS: Rheomex CTW 100 OS (Thermo Electron GmbH, Karlsruhe, Germany). The torque rheometer re-mixed the HDPE and the fibers while measuring the torque required at each step of blending.…”
Section: Methodsmentioning
confidence: 99%
“…This result is explained by the shear stress behavior during the mixing process. The internal mix slippage leads to more friction which contributes to the temperature increase [35]. Species and origin affected the wettability of the wood fiber and its incorporation in the polymer.…”
Section: Effect Of Wood Species and Originmentioning
confidence: 99%